2021
DOI: 10.31235/osf.io/ew9pn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overlooked and Unaddressed: A narrative review of mental health consequences of child marriages.

Abstract: Child Marriage (before the age of 18) affects over 12 million young women globally, annually. Despite acknowledgement of the negative impacts of the practice on reproductive health, mental health consequences are largely overlooked. Given the ability for poor mental health to intensify other health and social challenges, understanding the mental health consequences linked to child marriage is vital. Our study is the first to examine how mental health is approached in current literature on child marriage. Our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The solution to the aforementioned bad situation should be sought in the wider community, which unites economic, social, psychological, educational, pedagogical and family support with one common goal, which is to prevent minor (child) marriage by force, compulsion, decree and sanctions. 12 Research into underage marriages of girls in the era of the Covid-19 pandemic is particularly interesting. This is a highly representative sample of married and unmarried girls in India.…”
Section: Previous Researchmentioning
confidence: 99%
“…The solution to the aforementioned bad situation should be sought in the wider community, which unites economic, social, psychological, educational, pedagogical and family support with one common goal, which is to prevent minor (child) marriage by force, compulsion, decree and sanctions. 12 Research into underage marriages of girls in the era of the Covid-19 pandemic is particularly interesting. This is a highly representative sample of married and unmarried girls in India.…”
Section: Previous Researchmentioning
confidence: 99%
“…There is vast evidence that child marriage is associated with unwanted and adverse fertility outcomes, under utilization of antenatal care, and intimate partner violence [2]. Several studies also found negative impacts of child marriage on women's mental health conditions [3]. However, long term health consequences of child marriage, especially it's impact on chronic health outcomes and health risk behaviors, are relatively less explored.…”
Section: Introductionmentioning
confidence: 99%